2018
DOI: 10.1136/gutjnl-2017-315448
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin-activated hepatocellular carcinomas are addicted to fatty acids

Abstract: FAO induced by β-catenin oncogenic activation in the liver is the driving force of the β-catenin-induced HCC. Inhibiting FAO by genetic and pharmacological approaches blocks HCC development, showing that inhibition of FAO is a suitable therapeutic approach for -mutated HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
120
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 45 publications
8
120
2
2
Order By: Relevance
“…Typically, the β‐catenin‐activated HCCs carry an activating mutation in the CTNNB1 , a gene that encodes β‐catenin in the Wnt pathway, whose mutation is not uncommon (19.5%) in human HCC . Inhibiting FAO by genetic and pharmacological approaches blocks the HCC development, which suggests that inhibiting FAO is a suitable therapeutic approach for the β‐catenin‐mutated HCC . In addition, Iwamoto et al recently reported that HCC cells would rather utilize FAO for their survival under the hypoxic conditions induced by the antiangiogenic drugs.…”
Section: Altered Lipid Metabolism Of Hepatocellular Carcinoma Cellsmentioning
confidence: 99%
“…Typically, the β‐catenin‐activated HCCs carry an activating mutation in the CTNNB1 , a gene that encodes β‐catenin in the Wnt pathway, whose mutation is not uncommon (19.5%) in human HCC . Inhibiting FAO by genetic and pharmacological approaches blocks the HCC development, which suggests that inhibiting FAO is a suitable therapeutic approach for the β‐catenin‐mutated HCC . In addition, Iwamoto et al recently reported that HCC cells would rather utilize FAO for their survival under the hypoxic conditions induced by the antiangiogenic drugs.…”
Section: Altered Lipid Metabolism Of Hepatocellular Carcinoma Cellsmentioning
confidence: 99%
“…Beyond glycolysis, it is now well established that other pathways are hijacked in cancer cells to promote their growth 8. In their study, Senni et al 1 show that β-catenin-activated HCCs are not glycolytic because tumours induced by APC deletion do not display altered lactate production compared with adjacent non-tumour tissue. In line with this observation, they found that β-catenin overactivation in hepatocytes does not alter their glycolytic rate, nor does it change glutaminolysis.…”
mentioning
confidence: 99%
“…Various pathways are dysregulated in HCC, including p53 and other cell cycle regulators, chromatin modifiers, oxidative stress, insulin and growth factor signalling, and Wnt/β-catenin signalling. In this issue, Senni and colleagues1 demonstrate the role of fatty acid oxidation as a source of energy in the metabolic adaptation triggered by β-catenin oncogenic activation in hepatocytes. This work describes an atypical cancer cell addiction to fatty acids and represents an important discovery that may pave the way for novel therapeutics.…”
mentioning
confidence: 99%
See 2 more Smart Citations